Preparation method of ortho-parahydrogen conversion catalyst
By combining ultrasonic and mechanical dispersion techniques in the preparation of catalysts, spherical hydrated iron oxide particles are formed, which solves the problems of small specific surface area and large wear of the existing catalyst, and realizes the preparation of a high-efficiency and low-energy consumption positive hydrogen to secondary hydrogen conversion catalyst.
Patent Information
- Application Number
- CN202310935955.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
During the preparation process, the existing positive and secondary hydrogen conversion catalysts have problems such as small specific surface area, low physical strength, large wear, high energy consumption and low preparation efficiency, which is difficult to meet the rapid conversion of positive and secondary hydrogen to secondary hydrogen in liquid hydrogen production.
Using the method of simultaneous action of ultrasonic dispersion and mechanical dispersion, the iron-containing solution is mixed with the precipitant to form a colloidal mixture, followed by washing, drying, crushing and clay molding, and spherical catalyst particles are obtained by extrusion molding and rounding molding.
It improves the specific surface area and physical strength of the catalyst, reduces wear and energy consumption, improves preparation efficiency and catalytic activity, and is suitable for rapid conversion of positive hydrogen to secondary hydrogen.
Smart Images

Figure CN119425693A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation and relates to a method for preparing a catalyst for ortho-parahydrogen conversion. Background Art
[0002] Liquid hydrogen is a highly efficient liquid fuel with broad application prospects in chemical production, aerospace engineering, hydrogen-powered vehicles, etc. Liquid hydrogen has the advantages of being easy to store and measure, and has become one of the important ways to use, store and transport hydrogen energy.
[0003] A hydrogen molecule is composed of two hydrogen atoms with different nuclear spin directions, of which orthohydrogen is symmetrical and parahydrogen is antisymmetric. Both orthohydrogen and parahydrogen can exist stably in liquid and gaseous states, and their equilibrium concentrations are affected by temperature. At room temperature, the orthohydrogen content in hydrogen is 25% and the parahydrogen content is 75%, which is called normal hydrogen or standard hydrogen. When the temperature drops, orthohydrogen will spontaneously convert to parahydrogen. At the standard boiling point of liquid hydrogen, the parahydrogen content can reach 99.8%. In the absence of an external catalyst, the spontaneous conversion of the orthohydrogen to the parahydrogen state is very slow, and the heat released during the conversion process is greater than the vaporization heat of liquid hydrogen, which will cause vaporization loss of liquid hydrogen. In order to quickly complete the conversion of orthohydrogen to parahydrogen while liquefying hydrogen, the development of high-performance orthohydrogen conversion catalysts is crucial for the production of liquid hydrogen.
[0004] At present, amorphous hydrated iron oxide is mainly used as a catalyst for the conversion of normal para-hydrogen. CN202111354244.6 discloses a method for preparing a doped normal para-hydrogen conversion catalyst. Prepare an iron salt solution and a metal ion solution to be doped respectively, drip the metal ion solution to be doped into the iron salt solution in a certain proportion, add an appropriate amount of alkali solution, and wash, dry and grind the precipitate obtained by the hydrothermal reaction of the mixed solution to obtain irregularly shaped hydrated iron oxide particles. The particles have more edges and corners, lower strength, and greater wear when used as a catalyst. On the other hand, the doped iron oxide prepared by the high-temperature hydrothermal method in this method has a larger grain size (300~1000nm), a high product crystallinity, and a small specific surface area. At the same time, the high-temperature reaction time used is too long, the synthesis efficiency is low, and the energy consumption is high. CN202210832769.4 provides a normal para-hydrogen conversion catalyst and a preparation method. The catalyst is a fiber magnetic catalyst FeMnO doped with Fe atoms. x , having a fibrous structure with a diameter of 2 to 5 nm and a length of 100 nm to 500 nm, a large product particle size and a low specific surface area. This method requires the use of a hydrothermal reaction, which consumes a lot of energy, and because a manganese oxide precursor needs to be prepared, the preparation cost is also high.
[0005] CN201910782910.2 discloses a method for preparing hydrated iron oxide, adding a weakly basic compound to a ferric chloride solution, aging, filtering, and dispersing the filter cake in an ammonium bicarbonate solution, filtering, and drying to obtain hydrated iron oxide. The method uses a weak base as a precipitant, and the crystalline phase of the product obtained by the reaction at room temperature and pressure is mainly amorphous. The method reacts the filter cake with ammonium bicarbonate, and then uses the pore-forming effect of ammonium bicarbonate pyrolysis to increase the specific surface area of the product, but it will cause a significant decrease in the strength of the dried particles, and the particles have more edges and corners, resulting in greater wear. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a para-hydrogen conversion catalyst. The para-hydrogen conversion catalyst of the present invention has a large specific surface area, high physical strength, a simple preparation method, few catalyst particles, low energy consumption, high preparation efficiency, and high catalytic activity for para-hydrogen conversion.
[0007] The preparation method of the ortho-parahydrogen conversion catalyst of the present invention comprises the following contents: (1) Under the simultaneous action of ultrasonic dispersion and mechanical dispersion, the iron-containing solution and the precipitant are mixed to react to obtain a colloidal mixture, which is then allowed to stand for a period of time; (2) washing and separating the material obtained in step (1), and then drying it to obtain a weakly crystalline hydrated iron oxide material, and then crushing it and screening a powder of 500 to 1600 mesh; the drying treatment conditions are: drying temperature and time 10 to 90°C, drying time 12 to 120 hours, and drying atmosphere is air atmosphere; (3) The powder, clay and organic acid solution obtained in step (2) are fully mixed, kneaded, extruded and chopped, and then the strip material is re-formed into spherical particles using a spheronizer, and dried to obtain a catalyst.
[0008] In the method of the present invention, the reaction temperature in step (1) is 10-45° C., and the standing time is 0.5-5 hours.
[0009] In the method of the present invention, the iron-containing solution in step (1) is an aqueous solution of ferric chloride and / or ferric sulfate; the iron-containing solution is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.
[0010] In the method of the present invention, the precipitant in step (1) is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate aqueous solution; the concentration of the precipitant is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.
[0011] In the method of the present invention, the iron-containing solution in step (1) is Fe 3+ Calculate the precipitant with OH - The molar ratio is 3.0 to 4.5.
[0012] In the method of the present invention, the ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 KHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.
[0013] In the method of the present invention, the mechanical dispersion in step (1) includes but is not limited to any method and operating conditions that are conducive to rapid and uniform mixing of the materials, such as mechanical stirring, magnetic stirring, shaking table, shear stirring, etc.
[0014] In the method of the present invention, the order and method of adding the materials in step (1) are not particularly limited, but preferably the alkali solution is added to the iron salt solution, which can be added all at once or in batches, preferably in batches.
[0015] In the method of the present invention, the separation in step (2) can be carried out by natural sedimentation, centrifugation, vacuum filtration or filter press to separate the washed suspension into solid and liquid to obtain a solid phase.
[0016] In the method of the present invention, the degree of washing and filtering in step (2) must satisfy the requirement that the mass content of sodium in the catalyst composition obtained finally, calculated as Na2O, is less than 0.5%, preferably the Na2O content is less than 0.25%; and deionized water is used for the washing operation.
[0017] In the method of the present invention, the drying treatment in step (2) is further preferably: the drying temperature is 40-80° C. and the drying time is 12-24 hours.
[0018] In the method of the present invention, the pulverization in step (2) can be carried out by various means, such as rolling, ball milling, etc. The pulverization process should be carried out in such a way that the powder does not undergo any crystal form change.
[0019] In the method of the present invention, the clay described in step (3) includes kaolin, bentonite and processed derivatives thereof.
[0020] In the method of the present invention, the organic acid solution in step (3) is an aqueous solution of acetic acid, propionic acid, oxalic acid, or lemon, and its mass concentration is 2 wt% to 10 wt%.
[0021] In the method of the present invention, the amount of clay in step (3) is 5-25% by weight of the total amount of hydrated iron oxide and clay, and more preferably 10-20% by weight.
[0022] In the method of the present invention, the amount of the acid solution used in step (3) is based on the amount of the acid solution added to the mixture to be suitable for extrusion molding.
[0023] In the method of the present invention, the material in step (3) is further preferably added with 3-10% of organic additives accounting for the total amount of hydrated iron oxide and clay, including sesbania powder and cellulose.
[0024] In the method of the present invention, the kneading and extruding in step (3) are conventional operation processes. They can be carried out by using an extruder or other molding method. The obtained strip-shaped particles are cylindrical in shape. The radial dimension of the strip-shaped particles in the wet state is 0.5 to 1.0 mm, the axial dimension is 0.5 to 1.0 mm, and the ratio of the axial dimension to the radial dimension is 1:(1 to 2).
[0025] In the method of the present invention, the drying conditions in step (3) are: drying temperature of 140 to 300° C., and drying time of 6 to 36 hours.
[0026] In the method of the present invention, the spherical particles obtained after the spheronization in step (3) have a diameter of 0.3 to 0.6 mm after drying.
[0027] The ortho-parahydrogen conversion catalyst prepared by the method of the present invention is a spherical particle with a diameter of 0.30-0.90 mm, a crushing strength of 5-12 N / particle, and an abrasion loss of 0.05-0.20%. The specific surface area is 150-250 m 2 / g; the catalyst includes hydrated iron oxide and clay. Based on the total weight of the catalyst, the hydrated iron oxide accounts for 75% to 95%, the clay accounts for 5% to 25%, and the microscopic particle size of the hydrated iron oxide is 3 to 12 nm.
[0028] In the para-hydrogen conversion catalyst of the present invention, the hydrated iron oxide is in a weak crystalline state and has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.
[0029] When preparing hydrated iron oxide, the present invention always uses ultrasonic dispersion and physical dispersion to work together during the reaction process, and the dispersion is strengthened from the macroscopic and microscopic synergistic perspective, which can avoid the aggregation of colloids or precipitation to form larger particles, thereby maintaining a highly dispersed state, which is conducive to obtaining smaller reactant particles and improving the specific surface area of the product. The present invention can generate weakly crystalline hydrated iron oxide at room temperature through micro-area shearing and cavitation formed by ultrasound, which is found to be beneficial to improving the activity of the catalyst through experimental studies. The present invention crushes the weakly crystalline hydrated iron oxide into fine particles, uses clay as a binder, and an organic acid as a peptizing agent, extrudes and forms a spherical catalyst particle after secondary spheronization and drying, and the hydrated iron oxide particles distributed inside are beneficial to improving the porosity of the catalyst, which can increase the effective contact area between hydrogen molecules and the catalyst. The obtained spherical particles have higher strength, fewer edges and corners, and lower wear. The spherical catalyst of the present invention is excellent in activity for catalytic conversion of normal and secondary hydrogen. The present invention shapes the catalyst into a spherical shape, which helps to reduce the flow resistance of the device, and also has the advantages of convenient loading. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XRD spectrum of the weakly crystalline hydrated iron oxide obtained in Example 1.
[0031] Figure 2 This is the electron diffraction spectrum of the weakly crystalline hydrated iron oxide obtained in Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with the examples. The Na2O content in the catalyst is tested by XRF method; the hydrated iron oxide (in terms of Fe2O3) content in the catalyst is tested by XRF method. The specific surface area is tested by low-temperature nitrogen adsorption method, and the specific surface area value is calculated according to the BET method; the nanoparticle size and lattice image of iron oxide are observed by transmission electron microscopy. The radial crushing strength of the strip sample is tested according to Chapter 5.11 of the HG / T 3927-2007 method. Abrasion is tested according to HG / T2976-1999. The method for determining the degree of crystallinity of a sample is defined as follows: (1) For a strongly crystalline sample, in its XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is at least one diffraction peak whose ratio is greater than 2, and the half-height width of the diffraction angle 2θ is less than 2º; (2) For a weakly crystalline sample, there is no diffraction peak in its XRD spectrum that meets the above-mentioned strong crystallization determination conditions, but there should be discernible lattice fringes in the high-magnification transmission electron microscope image, or discernible diffraction spots or diffraction rings in the electron diffraction spectrum. The ortho-parahydrogen content is calculated by gas chromatography, and the parahydrogen conversion rate is calculated as: conversion rate = (parahydrogen content% - 25%) / 25.8%, where the ortho-hydrogen and para-hydrogen contents of the raw hydrogen are calculated as 75% and 25% respectively, and the para-hydrogen equilibrium concentration is calculated as 50.8% at liquid nitrogen temperature (77K). The invention discloses an application of the para-hydrogen conversion catalyst in the para-hydrogen conversion reaction, wherein the reaction conditions are as follows: the activation conditions are vacuum drying at 120-160°C for 6-12 hours, the evaluation temperature is 77K, and the volume space velocity is 350min -1 . Example 1
[0033] Prepare 1.2 mol / L sodium hydroxide solution and 0.5 mol / L ferric chloride solution respectively. At room temperature (25°C), under the conditions of mechanical stirring and ultrasonic dispersion (40kHz, 20W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 2 hours, it is repeatedly washed with water and filtered to remove the sodium ions in the sample to meet the index requirements. The washed material is dried in a blast oven at 50°C for 12 hours to obtain hydrated iron oxide. It is crushed with a pulverizer, and the powder of 700-900 mesh is screened and mixed evenly with white clay. An appropriate amount of 5% propionic acid solution is added. After kneading, extrusion, and short cutting, the material is secondary molded into spherical particles using a spheronizer. Afterwards, at 140 o C for 12 hours to obtain the spherical normal-para hydrogen conversion catalyst of the present invention.
[0034] The obtained spherical normal-parahydrogen conversion catalyst particles have a diameter of 0.5 mm, a radial crushing strength of 6.4 N / particle, and a specific surface area of 215 m 2 / g. The mass content of hydrated iron oxide is 86%, the attrition is 0.12%, the microscopic particle size is 6.6nm, and it has a weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 2
[0035] Prepare 1.5 mol / L sodium hydroxide solution and 1.0 mol / L ferric chloride solution respectively. At room temperature (30°C), under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (100 KHz, 100 W / L), add a certain amount of ferric chloride solution to the sodium hydroxide solution to meet the OH content in the system. - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 4 hours, the suspension is repeatedly washed and filtered with water to remove the sodium ions in the sample so that it meets the index requirements. The washed material is dried in a blast oven at 60°C for 12 hours, and then dried at 160°C for 12 hours to obtain the hydrated iron oxide. It is crushed with a pulverizer, and the powder of 800 to 1000 mesh is screened and mixed evenly with bentonite. An appropriate amount of 5% acetic acid solution is added. After kneading and cutting into strips, the material is secondary molded into spherical particles using a spheronizer. Afterwards, at 160 o C for 10 hours to obtain the spherical normal-para hydrogen conversion catalyst of the present invention.
[0036] The obtained spherical ortho-parahydrogen conversion catalyst particles have a diameter of 0.4 mm, a radial crushing strength of 5.5 N / particle, and a specific surface area of 233 m 2 / g. The mass content of hydrated iron oxide is 90%, the attrition is 0.10%, the microscopic particle size is 6.2nm, and it has a weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 3
[0037] Prepare 1.5 mol / L sodium carbonate solution and 1.0 mol / L ferric chloride solution respectively. At 45°C, under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (40 kHz, 100 W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+The molar ratio is 3.5, and a suspension is formed. After standing for 0.5 hours, the suspension is repeatedly washed and filtered with water to remove the sodium ions in the sample so that it meets the index requirements. The washed material is dried in a blast oven at 80°C for 10 hours, and then dried at 105°C for 12 hours to obtain the hydrated iron oxide. It is crushed with a pulverizer, and the powder of 1200-1400 mesh is screened and mixed evenly with bentonite. An appropriate amount of 3% propionic acid solution is added. After kneading, extrusion, and short cutting, the material is secondary molded into spherical particles using a spheronizer. Afterwards, at 130 o C for 15 hours to obtain the spherical normal-para hydrogen conversion catalyst of the present invention.
[0038] The obtained spherical normal-parahydrogen conversion catalyst particles have a diameter of 0.9 mm, a radial crushing strength of 8.8 N / mm, and a specific surface area of 248 m 2 / g. The mass content of hydrated iron oxide is 75%, the attrition is 0.18%, the microscopic particle size is 6.5nm, and it has a weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Comparative Example 1
[0039] According to the method provided in Example 1 of CN202111354244.6, iron oxide was prepared. The obtained doped iron oxide had a grain size of 300-1000 nm, and the iron oxide showed strong crystallinity. The tested specific surface area was only 50 m 2 / g. The obtained irregular particles have more edges and corners, and the abrasion loss is 0.43%. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 2
[0040] Iron oxide was prepared according to the method provided in Example 1 of CN202210029537.5. The iron oxide grain size was 23 nm and the crystallinity was high. After testing, its specific surface area was only 66 m 2 / g. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 3
[0041] Hydrated iron oxide was prepared according to the method provided in Example 1, but without adding clay for molding. It could barely be extruded into strips. When the spheronization mechanism was continued to be used to form balls, the balls were easily broken apart, and the abrasion loss was 0.38%.
[0042] Table 1 Parahydrogen conversion rate of catalysts Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Parahydrogen conversion rate % 97.5 97.6 98.2 88.6 90.1
Claims
1. A method for preparing a catalyst for ortho-parahydrogen conversion, characterized in that The invention comprises the following contents: (1) mixing an iron-containing solution and a precipitant under the action of ultrasonic dispersion and mechanical dispersion to obtain a colloidal mixture, and then standing the mixture for a period of time; (2) washing and separating the material obtained in step (1), and then drying the material to obtain a weakly crystalline hydrated iron oxide material, and then crushing and screening a powder of 500 to 1600 mesh; the drying treatment conditions are: a drying temperature of 10 to 90° C., a drying time of 12 to 120 hours, and an air atmosphere; (3) fully mixing the powder obtained in step (2), clay, and an organic acid solution, kneading, extruding, and chopping the mixture, and then using a spheronizer to secondary mold the strip material into spherical particles, and drying to obtain a catalyst.
2. The method according to claim 1, characterized in that: The reaction temperature in step (1) is 10-45°C; the standing time is 0.5-5 hours.
3. The method according to claim 1, characterized in that: The iron-containing solution in step (1) is an aqueous solution of ferric chloride and / or ferric sulfate; the iron-containing solution is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.
4. The method according to claim 1, characterized in that: The precipitant in step (1) is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate aqueous solution; the concentration of the precipitant is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.
5. The method according to claim 1, characterized in that: The iron-containing solution in step (1) is Fe 3+ Calculate the precipitant with OH - The molar ratio is 3.0 to 4.
5.
6. The method according to claim 1, characterized in that: The ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 kHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.
7. The method according to claim 1, characterized in that: The drying conditions in step (2) are as follows: drying temperature at 40-80°C and drying time at 12-24 hours.
8. The method according to claim 1, characterized in that: The organic acid solution in step (3) is one or more of acetic acid, propionic acid, oxalic acid and lemon water solution, and the concentration of the organic acid solution is 2wt% to 10wt%.
9. The method according to claim 1, characterized in that: The amount of clay in step (3) is 5% to 25% by weight of the total amount of hydrated iron oxide and clay, and more preferably 10% to 20%.
10. The method according to claim 1, characterized in that: The drying conditions in step (3) are: drying temperature 140-300° C., and drying time 6-36 hours.
11. A catalyst for the conversion of normal and secondary hydrogen prepared by the method according to any one of claims 1 to 10, characterized in that: The catalyst is spherical particles with a diameter of 0.30-0.90 mm, a crushing strength of 5-12 N / particle, an abrasion loss of 0.05-0.20%, and a specific surface area of 150-250 m 2 / g.
12. The catalyst according to claim 11, characterized in that: The catalyst comprises hydrated iron oxide and clay. Based on the total weight of the catalyst, the hydrated iron oxide accounts for 75% to 95% and the clay accounts for 5% to 25%. The microscopic particle size of the hydrated iron oxide is 3 to 12 nm. The hydrated iron oxide is in a weak crystalline state and has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.
Citation Information
Patent Citations
Preparation method of hydrated iron oxide
CN110422886A
A catalyst for converting normal and para hydrogen suitable for wide range of low temperature conditions and preparation method thereof
CN115920919B
Para-hydrogen enrichment device and method for nuclear magnetic resonance para-hydrogen induced polarization
CN110568000A
Supported ortho-parahydrogen conversion catalyst and preparation method thereof
CN112044457A
Orthohydrogen and parahydrogen conversion catalyst for liquid hydrogen conversion and preparation method thereof
CN113797928A